2014
DOI: 10.3988/jcn.2014.10.2.166
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Peripheral and Central Nervous Systems in a Valosin-Containing Protein Mutation

Abstract: BackgroundInclusion-body myopathy with Paget's disease of the bone and frontotemporal dementia (IBMPFD) is a rare, late-onset autosomal disorder arising from missense mutations in a gene coding for valosin-containing protein.Case ReportWe report the case of a man carrying the previously described p.Arg159His mutation, who had an unusual axonal sensorimotor neuropathy as the first clinical manifestation of IBMPFD, and for whom diagnosis only became clear 8 years later when the patient developed frontotemporal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…3 The p.Arg159His mutation has previously been reported to be pathogenic in the heterozygous state in multiple unrelated families showing intrafamilial and interfamilial phenotypic variability, encompassing IBM, PDB, FTD, and amyotrophic lateral sclerosis, which is typical for MSP1, without complete penetrance. [8][9][10][11][12][13] Muscle MRI revealed an asymmetric and patchy pattern of muscle involvement in patients A and B, with paraspinal and lower limb muscles being preferentially involved. This patchy involvement has been described previously and seems to contrast with the selective patterns of muscle involvement in muscular dystrophies and sporadic IBM (sIBM).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3 The p.Arg159His mutation has previously been reported to be pathogenic in the heterozygous state in multiple unrelated families showing intrafamilial and interfamilial phenotypic variability, encompassing IBM, PDB, FTD, and amyotrophic lateral sclerosis, which is typical for MSP1, without complete penetrance. [8][9][10][11][12][13] Muscle MRI revealed an asymmetric and patchy pattern of muscle involvement in patients A and B, with paraspinal and lower limb muscles being preferentially involved. This patchy involvement has been described previously and seems to contrast with the selective patterns of muscle involvement in muscular dystrophies and sporadic IBM (sIBM).…”
Section: Discussionmentioning
confidence: 99%
“…Yet, the onset age of the myopathy phenotype is rather early for this age-related disorder compared to patients harboring the same p.Arg159His mutation and indeed the complete group of patients with MSP1; the mean age at onset is ≈40 to 45 years, with few patients being in their 20s. 2,3,[8][9][10][11][12]26 Notably, CK levels for the index patient are markedly elevated (1138 U/L), contrasting with CK levels generally reported to be normal or mildly elevated in VCP-related myopathies. 3,4 Besides these anomalies, the 2 key features of VCP-related disease are preserved, i.e., the slowly progressive, age-related nature of the disorder and the tissue-specific phenotype.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We performed a literature review on the clinical and genetic characteristics of previously reported ALS‐VCP cases (Table S1), 2,4–7,16,23–33 and illustrated mutation sites in VCP associated with ALS, IBMPFD, and other phenotypes (Figure S1). 2–5,7,16,20–86 A total of 59 cases have been reported, with the disease typically developing in patients in their 40s–50s, and 14 of the 33 cases survived without artificial respiration for more than five years. Given that the epidemiological studies of general ALS suggest that the peak prevalence is observed in patients in their 70s–80s, and that the median survival time is two to four years, 87–91 the ALS‐VCP cases might be characterized by relatively early disease onset and slow disease progression.…”
Section: Discussionmentioning
confidence: 99%